Elucidating the contribution of the elemental composition of fetal calf serum to antigenic expression of primary human umbilical-vein endothelial cells in vitro. Issue 3 (14th January 2011) - Bryan, Nicholas; Andrews, Kirstie D.; Loughran, Michael J.; Rhodes, Nicholas P.; Hunt, John A.
Abstract : One of the major obstacles to obtaining human cells of a defined and reproducible standard suitable for use as medical therapies is the necessity for FCS (fetal calf serum) media augmentation in routine cell culture applications. FCS has become the supplement of choice for cell culture research, as it contains an array of proteins, growth factors and essential ions necessary for cellular viability and proliferation in vitro . It is, however, a potential route for the introduction of zoonotic pathogens and makes defining the cell culture milieu impossible in terms of reproducibility, as the precise composition of each batch of serum not only changes but is in fact extremely variable. The present study determined the magnitude of donor variations in terms of elemental composition of FCS and the effect these variations had on the expression of a group of proteins associated with the antigenicity of primary human umbilical-vein endothelial cells, using a combination of ICPMS (inductively coupled plasma MS) and flow cytometry. Statistically significant differences were demonstrated for a set of trace elements in FCS, with correlations made to variations in antigenic expression during culture. The findings question in detail the suitability of FCS for the in vitro supplementation of cultures of primary human cells due to the lack of reproducibility and modulations in protein expression when cultured in conjunction with sera from xenogeneic donors.